The relationship between spirituality and quality of life in patients with breast cancer - Silva, Lure Êmilly Barreto da; Costa, Higor Siqueira; Nascimento, Evelyn Cristine; Freitas, Vitória Gomes de; Rocha, Marina Elias (Mastology, 2026)
Objective: To discuss the relationship between spirituality and quality of life in patients with breast cancer. Methods: A search was conducted on the SciELO and PubMed databases for original articles in Portuguese and English, published between 2023 and 2025, and using the descriptors “breast neoplasms” and “spirituality”. Seventeen articles were found, of which four were selected for review. Results: Worldwide, breast cancer is the most common neoplasm among women and brings intense and long-lasting physical, social, and above all, emotional challenges to diagnosed patients. The scope of spirituality in patients with breast cancer is necessary since it offers support, consolation, and purpose through a new meaning of existence, in order to combat insecurities and fears associated with the disease. Consequently, it strengthens the patient’s emotional aspect and ensures a better quality of life. In this sense, for cancer patients, spirituality acts to help the patient deal with the profound hopelessness that comes with the onset of the disease and proposes a new perspective on coping with breast cancer, in order to improve the patient’s psychological well-being and quality of life. Conclusion: The treatment of any and all pathologies is the result of the complex interaction between biological, clinical, and psychosocial factors. Based on this, the exercise of spirituality has been shown to be an important component in the treatment of patients with breast cancer by promoting comfort, encouragement, and support during the disease process, which positively impacts the patient’s quality of life and psychosocial well-being.